IMPROVING THE STUDENTS’ READING SKILL THROUGH CLOZE PROCEDURE TECHNIQUE - HENDRA EKA PUTRA (Ta'dib, 2010)
Lack of ability in comprehending English texts is students’ big problem nowadays. They fail in comprehending or grasping information from reading materials. As a result, their motivation decreases which in turn can inhibit their reading comprehension. In reading comprehension class, those difficulties faced by the students may be caused by many factors such as, reading materials, teaching method, media used and so forth. Related to the problem, cloze procedure technique can be used as an alternative technique for teaching reading. And, under the teacher’s supervision the students also can enrich their reading skill, even their English vocabulary through this technique.Kata kunci: reading, reading skill, cloze procedure, technique